Bifunctional Nanocomposites Based on SiO2/NiS2 Combination for Electrochemical Sensing and Environmental Catalysis. Issue 1 (10th November 2021) - Renganathan, Vengudusamy; Balaji, Ramachandran; Chen, Shen‐Ming; Chandrasekar, Narendhar; Maheshwaran, Selvarasu; Kao, C. R.
Abstract: Due to a rapid growth in the industrial processing of the large amount of raw materials have caused a severe contamination of dihydroxy benzene‐based isomers and various colored dyes in the environment. For the highly sustainable environment supporting a healthy human life, the development of highly reliable sensor for the determination and elimination of pollutants is of greater importance. Coupling with enhanced sensing performance, the sensor should also be portable, economical and reproducible. Within consideration of the facts, we fabricate a novel electrochemical sensor for the determination of dihydroxy benzene (catechol) based on the bimetallic nanocomposites SiO2 /NiS2 (SN). We utilized the amperometric analytical technique for the effective sensing of catechol at the lower concentration. This technique is economical and ultrasensitive to others. The fabricated bimetallic nanocomposites SiO2 /NiS2 reinforced electrode showed a good sensitivity 1.719 μA μM −1 cm −2 and limit of detection (LOD) 24.2 nM with the linear range of 0.2 μM to 43.2 μM. Then the bimetallic nanocomposites SN is used for the investigation of removal of methyl orange dye. The SN accelerated the degradation of methyl orange in 8 mins. Abstract :